Metabolic Changes in the Trichomes of Cannabis sativa var. bedrobinol Analyzed by 1H-NMR-Based Metabolomics - Nizar Happyana; Oliver Kayser (Universitas Gadjah Mada, 2020)
Trichomes of Cannabis sativa are the main tissue for synthesizing and storing cannabinoids, the most interesting compounds in this plant. In this report, metabolic changes in the trichomes of C. sativa var. bedrobinol were investigated by 1H-NMR-based metabolomics over the flowering session. Three cannabinoids, including Δ9-tetrahydrocannabinolic acid (THCA), cannabichromenic acid (CBCA), and Δ9-tetrahydrocannabinol (THC), were successfully identified in the chloroform extracts of the Cannabis trichomes. Meanwhile, 20 non-cannabinoid compounds, including sugars, amino acids, and other acidic constituents, were detected in the water extracts. Metabolic changes of the Cannabis trichomes during the monitoring time were successfully revealed using the models of partial least squares discriminant analysis (PLSDA) and 1H-NMR quantitative analysis. Score plots of the PLSDA models classified metabolomes based on the harvest time. Discriminant metabolites for the differentiation were detected in the loading plots of the models. THCA was found as an important discriminant compound in the chloroform extracts, while all quantified water-soluble compounds were detected, contributing to the metabolic changes of the water extracts. The obtained results shed more light on the biosynthesis of metabolites in the Cannabis trichomes over the flowering season.